Efavirenz concentrations in CSF exceed IC50 for wild-type HIV - Best, B. M.; Koopmans, P. P.; Letendre, S. L.; Capparelli, E. V.; Rossi, S. S.; Clifford, D. B.; Collier, A. C.; Gelman, B. B.; Mbeo, G.; McCutchan, J. A.; Simpson, D. M.; Haubrich, R.; et al. (Journal of antimicrobial chemotherapy, 2011)
HIV-associated neurocognitive disorders remain common despite use of potent antiretroviral therapy (ART). Ongoing viral replication due to poor distribution of antivirals into the CNS may increase risk for HIV-associated neurocognitive disorders. This study's objective was to determine penetration of a commonly prescribed antiretroviral drug, efavirenz, into CSF. CHARTER is an ongoing, North American, multicentre, observational study to determine the effects of ART on HIV-associated neurological disease. Single random plasma and CSF samples were drawn within 1 h of each other from subjects taking efavirenz between September 2003 and July 2007. Samples were assayed by HPLC or HPLC/mass spectrometry with detection limits of 39 ng/mL (plasma) and <0.1 ng/mL (CSF). Eighty participants (age 44 ± 8 years; 79 ± 15 kg; 20 females) had samples drawn 12.5 ± 5.4 h post-dose. The median efavirenz concentrations after a median of 7 months [interquartile range (IQR) 2-17] of therapy were 2145 ng/mL in plasma (IQR 1384-4423) and 13.9 ng/mL in CSF (IQR 4.1-21.2). The CSF/plasma concentration ratio from paired samples drawn within 1 h of each other was 0.005 (IQR 0.0026-0.0076; n = 69). The CSF/IC(50) ratio was 26 (IQR 8-41) using the published IC(50) for wild-type HIV (0.51 ng/mL). Two CSF samples had concentrations below the efavirenz IC(50) for wild-type HIV. Efavirenz concentrations in the CSF are only 0.5% of plasma concentrations but exceed the wild-type IC(50) in nearly all individuals. Since CSF drug concentrations reflect those in brain interstitial fluids, efavirenz reaches therapeutic concentrations in brain tissue.